تقيم نوعية المياه للري والترب المتأثره بالملوحة في اهوار ذي قار - عبد الرضا ساهر (University of Thi-Qar Journal of Science, 2008)
This study included collection of 10 samples of water from many locations of Thi-Qar Marshes during July 2006 for evaluation of the water of some stations for irrigation use and classification of their soils . There for the electrical conductivity ( EC ) , calcium (Ca) , magnesium ( Mg ) , chloride ( Cl ) , biocarbonate ( HCO3 ) , sodium ( Na ) , boron ( B ) ions , were determined . The results were : (1220-12250)mmos/cm , (57.6-530) , (14.86-416.6) , (160-273) , (126-943) , (0.23-0.91) , (140-655) mg/lrespectively . The results showed that there were Sodium and salinity hazard in the water and the soils of some stations except the soil of the AlMajari area is not salinity.